Peran Ukuran Perusahaan dalam Memoderasi Hubungan Profitabilitas, Likuiditas dan Struktur Modal dengan Kualitas Laba - Suriani Br. Ginting; Anita Tarihoran; Robinhot Gultom (Universitas Methodist Indonesia, 2024)
This research aims to determine and analyze the role of company size in moderating the relationship between profitability, liquidity capital structure, and earnings quality. The research object is a manufacturing company listed on the Indonesia Stock Exchange for the 2017-2021 period. The sampling technique was carried out using purposive sampling and a sample of 72 companies was obtained. The data analysis method is multiple linear regression analysis and absolute difference value testing using the SPSS data processing application. The research results show that capital structure has a significant effect on earnings quality, but profitability and liquidity do not have a significant effect on earnings quality. The results of the moderation test show that company size is unable to moderate the relationship between profitability, liquidity capital structure, and earnings quality.